1998
DOI: 10.1080/10495399809525887
|View full text |Cite
|
Sign up to set email alerts
|

Partial cloning and expression of the bovine leptin gene

Abstract: The product of the leptin (i.e., obese) gene may be an important regulator of energy metabolism, adiposity, and reproduction, and is perhaps linked to meat quality determinants such as marbling. Molecular probes were developed using polymerase chain reaction (PCR) technology to evaluate leptin expression in adipose depots and to evaluate the tissue-dependent nature of expression reported in other species. A 438 bp fragment representing the coding region of the bovine leptin gene excluding the N-terminal secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 13 publications
2
35
0
3
Order By: Relevance
“…Furthermore, mRNA studies demonstrated that the ruminant leptin gene is specifically expressed in adipose tissues (Dyer et al 1997b, Ji et al 1998, Tsuchiya et al 1998 and is related to feeding level (Bocquier et al 1998, Kumar et al 1998. Leptin gene expression is also modulated by daylength in sheep, independently of food intake, adiposity and reproductive activity (Bocquier et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mRNA studies demonstrated that the ruminant leptin gene is specifically expressed in adipose tissues (Dyer et al 1997b, Ji et al 1998, Tsuchiya et al 1998 and is related to feeding level (Bocquier et al 1998, Kumar et al 1998. Leptin gene expression is also modulated by daylength in sheep, independently of food intake, adiposity and reproductive activity (Bocquier et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The cloning and sequencing of ovine and bovine leptin cDNA (Dyer et al 1997b, Ji et al 1998 revealed that their coding region has 86 and 87% homology, respectively, with the human sequence. Furthermore, mRNA studies demonstrated that the ruminant leptin gene is specifically expressed in adipose tissues (Dyer et al 1997b, Ji et al 1998, Tsuchiya et al 1998 and is related to feeding level (Bocquier et al 1998, Kumar et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the plasma concentration of leptin, a protein hormone secreted almost exclusively by adipocytes (Zhang et al 1994, Friedman & Halaas 1998, Ji et al 1998, Ahima & Flier 2000, could also be an important adaptation, particularly given the role of WAT in support of early lactation in dairy cattle. In ruminants and other animals, leptin is synthesized in proportion to the overall degree of adiposity (Friedman & Halaas 1998, Ahima & Flier 2000, Blache et al 2000, Delavaud et al 2000, Ehrhardt et al 2000, and acts on the central nervous system (CNS) to reduce voluntary feed intake (Friedman & Halaas 1998, Henry et al 1999, Ahima & Flier 2000, Schwartz et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on complementary DNA (cDNA) cloning of leptin in various species [8,13,15,19,23], and we also reported cDNA cloning of canine leptin and the activity of its recombinant protein [14]. In this study, we cloned feline leptin cDNA using reverse transcription-polymerase chain reaction (RT-PCR) and examined tissue distribution of its mRNA by RT-PCR analysis.…”
mentioning
confidence: 99%